Regulation of P2X3 Receptor Structure and Function - Fabbretti, Elsa; Nistri, Andrea (CNS & Neurological Disorders - Drug Targets, 2012)
The strong expression of ATP-gated P2X3 receptors by a subpopulation of sensory neurons indicates the important role of these membrane proteins in nociceptive signaling in health and disease, especially when the latter is accompanied by chronic pain syndromes. Molecular and cell biology studies have shown that these receptors exist mainly as trimeric homomers, and, in part, as heteromers (assembly of two P2X3 subunits with one P2X2). Recent investigations have suggested distinct molecular determinants responsible for agonist binding and channel opening for transmembrane flux of sodium, calcium and potassium ions. Trimeric P2X3 receptors are rapidly activated by ATP and can be strongly desensitized in the continuous presence of the agonist. Thus, the factors controlling the degree of desensitization and the time necessary to recover from it are essential elements to determine how efficiently and how often the P2X3 receptor can signal pain. Endogenous substances, widely thought to be involved in triggering pain especially in pathological conditions, can potently modulate the expression and function of P2X3 receptors, with differential changes in response amplitude, desensitization and recovery. Hence, studying P2X3 receptors can lead not only to the design of novel antagonists as analgesics, but also to identify intracellular interactors that may be targeted to downregulate P2X3 receptors. Strong facilitation of P2X3 receptor function is induced by endogenous substances like the neuropeptide calcitonin gene-related peptide and the neurotrophins nerve growth factor and brain-derived neurotrophic factor. These substances possess distinct mechanisms of action on P2X3 receptors, generally attributable to discrete phosphorylation of N- or C-terminal P2X3 domains.
Keywords: Brain-derived neurotrophic factor